2021
DOI: 10.1186/s12890-021-01543-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of body composition parameters in the study of the association between body composition and pulmonary function

Abstract: Background The excess adiposity, even in the absence of diseases, is responsible for a decline in pulmonary function, which is considered a predictor of mortality and a risk factor for diseases in several epidemiological studies. However, studies on the association between obesity and pulmonary function have found only few associations or inconclusive results. The aim of the study is to evaluate the association between body composition and spirometric parameters, comparing simple obesity measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Furthermore, in a 2016 study of 617 participants, the mild COPD group (72 participants) showed an even higher mean decline in FEV1 (129 mL/year) [55]. In a 2021 cohort study of 1746 participants, each 1-cm increase in WC decreased FEV1 by 6 mL in men and by 2 mL in women [56]. In addition, in the Coronary Artery Risk Development in Young Adults (CARDIA) study, the mean decline in FEV1 among participants with a baseline BMI ≥ 26.4 kg/m 2 was 6.4 mL/year [57].…”
Section: Discussionmentioning
confidence: 93%
“…Furthermore, in a 2016 study of 617 participants, the mild COPD group (72 participants) showed an even higher mean decline in FEV1 (129 mL/year) [55]. In a 2021 cohort study of 1746 participants, each 1-cm increase in WC decreased FEV1 by 6 mL in men and by 2 mL in women [56]. In addition, in the Coronary Artery Risk Development in Young Adults (CARDIA) study, the mean decline in FEV1 among participants with a baseline BMI ≥ 26.4 kg/m 2 was 6.4 mL/year [57].…”
Section: Discussionmentioning
confidence: 93%
“…The use of regression analysis makes it possible to create mathematical equations for determining the appropriate parameters of various organs and systems [3,11,18], in particular for spirometric forecasting, where predictors are anthropometric and somatotypological variables [4,7]. Despite the fact that there are separate works in which mathematical modeling of external breathing indicators is performed [1,8,15], this does not negate the expediency of such studies, especially for certain ethno-territorial population groups of a certain age, sex, health status, constitutional type, because it will make it possible to establish reference values of spirometric parameters.…”
Section: Discussionmentioning
confidence: 99%
“…The practical importance of using mathematical modeling to determine the reference values of spirographic parameters is emphasized by many researchers who draw attention to the need to take into account the factor of sex and age [4,7,15]. Unfortunately, there are no works that study the complex influence of all anthropometric and somatotypological indicators on spirometric parameters in healthy young people.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…COPD is a chronic inflammatory lung disease which is considered a systemic disease 15 . Multi-morbidity including hormonal, metabolic and musculoskeletal derangements are common [16][17][18] . In the context of critical illness, COPD represents an independent risk factor for unfavourable outcomes including increased length of ICU stay, prolonged ventilator weaning, muscle wasting and interrupted skin integrity 19 , ICU readmission, and death 14,20,21 .…”
Section: Introductionmentioning
confidence: 99%